Cereal rye cover crop terminated at crop planting reduces early‐season weed density and biomass in Wisconsin corn–soybean production. Issue 1 (18th February 2022) - Grint, Kolby R.; Arneson, Nicholas J.; Oliveira, Maxwel Coura; Smith, Daniel H.; Werle, Rodrigo
Abstract: A fall‐established cereal rye ( Secale cereale L.) cover crop has potential to provide weed suppression in fields that will be planted with corn ( Zea mays L.) and/or soybean [ Glycine max (L.) Merr.], reducing the selection pressure for herbicide resistance as part of an integrated weed management approach. However, biomass from an overwintering cover crop can be limited in areas with prolonged cool‐spring growing conditions, like in the Upper Midwest region of the United States. This study was conducted to determine if a cereal rye cover crop grown in Wisconsin and terminated at the time of crop planting could provide effective levels of early‐season weed suppression in corn–soybean systems practicing no‐till soil management. Cover crop biomass, weed biomass, and weed density were assessed at two Wisconsin locations (eight site‐crop‐years total; four site‐years of each corn and soybean) in 2019 and 2020. Cereal rye biomass production at the time of crop planting ranged from 290–1, 480 kg ha –1 . Overall, no‐till management with a cover crop reduced weed density by 31% and reduced weed biomass by 61% compared with no‐till without a cover crop. These results indicate that the use of a cereal rye cover crop in the Upper Midwest has potential to reduce the exclusive reliance on spring burndown herbicides in no‐till, but limited spring cover crop biomass in this region may diminish the weed‐suppressive effects from this management practice compared with other parts of the United States where higher amounts of cover crop biomass can be achieved at crop planting time. Core Ideas: Fall‐planted cereal rye biomass produced was <1, 500 kg ha −1 for late‐May termination. Cereal rye cover crop terminated in late May reduced weed density and biomass. Little cover crop biomass production may limit weed suppression in Wisconsin.